1985
DOI: 10.1002/1097-0142(19850401)55:7<1473::aid-cncr2820550709>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic studies in multiple myeloma. II. Immunoglobulin allotype associations

Abstract: A weakly positive but statistically significant association between HLA‐Cw5 and myeloma has been reported in black patients. The authors attempted to determine whether immunoglobulin allotypes of the Gm series demonstrate any such association. They were identified in the sera of 29 black patients and 160 healthy black control subjects by a standard hemagglutination‐inhibition technique. The results indicate that the G3m(g5) allotype is significantly associated with myeloma. Furthermore, addition of that immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This is quite analogous to the situation for the inducible mouse myeloma tumor wherein tumors can be induced with chronic immune stimuli and irritants only in certain genetically predisposed species of mice [7,8]. It is also compatible with the evidence that there is at least some genetic component to the etiology of myeloma in man [7,13,15,26]. The possibility of an actual protective effect from manifestations of such prior exposure in patients destined to have myeloma is suggested, but only weakly.…”
Section: Discussionsupporting
confidence: 69%
“…This is quite analogous to the situation for the inducible mouse myeloma tumor wherein tumors can be induced with chronic immune stimuli and irritants only in certain genetically predisposed species of mice [7,8]. It is also compatible with the evidence that there is at least some genetic component to the etiology of myeloma in man [7,13,15,26]. The possibility of an actual protective effect from manifestations of such prior exposure in patients destined to have myeloma is suggested, but only weakly.…”
Section: Discussionsupporting
confidence: 69%
“…A recent study suggested a link between MGUS/MM and chronic immune stimulation due to autoimmune diseases, acquired infections, and inflammatory conditions . Other studies have linked specific human leukocyte antigens (HLAs) (HLA‐Bw65, HLA‐Cw5, and HLA‐DRw14) to MM . Recently, hyperphosphorylated paratarg‐7, a defined autosomal dominantly inherited risk factor for MGUS and MM, was found in 11 of 100 African American (11.0%), 8 of 550 European (1.5%), and 1 of 278 Japanese (0.4%) healthy controls ( P <.001), suggesting a genetic predisposition in black individuals .…”
Section: Introductionmentioning
confidence: 99%
“…The increased frequency of a Gm allotype in a group of patients susceptible to a particular disease may be related to the allotype itself or to the haplotype containing it (Whittingham & Propert, 1986). Myeloma has been found to be associated with a low frequency of G1m(f) in an Irish population (Blake & Greally, 1975) and with a high frequency of G3m(g5) in black Americans (Leech et al ., 1985). However, the relationship between the Gm haplotype, which represents the inherited combination of Gm allotypes, and the Gm allotype expressed on the IgG paraprotein, which reflects the enhanced gene expression within the haplotype in multiple myeloma, has remained undetermined.…”
Section: Discussionmentioning
confidence: 99%